# SOLVING LOGARITHMIC EQUATIONS WORKSHEET

Solving Logarithmic Equations Worksheet :

Worksheet given in this section will be much useful for the students who would like to practice problems on solving logarithmic equations.

Before look at the worksheet, if you would like to know more about logarithms,

## Solving Logarithmic Equations Worksheet - Problems

Problem 1 :

Solve for x :

log2x  =  1/2

Problem 2 :

Solve for x :

log1/5x  =  3

Problem 3 :

Solve for x :

logx125√5  =  7

Problem 4 :

Solve for x :

logx0.001  =  -3

Problem 5 :

Solve for x :

log5(5log3x)  =  2

Problem 6 :

Solve for x :

x + 2log279  =  0

Problem 7 :

If 2logx  =  4log3,  then find the value of x.

Problem 8 :

If 3x is equal to log(0.3) to the base 9, then find the value of x.

Problem 9 :

Solve for x :

log5 √(7x - 4) - 1/2  =  log5 √(x + 2)

Problem 10 :

Solve for x :

log3x + log9x + log81x  =  7/4 ## Solving Logarithmic Equations Worksheet - Solutions

Problem 1 :

Solve for x :

log2x  =  1/2

Solution :

log2x  =  1/2

Convert to exponential form.

x  =  21/2

x  =  √2

Problem 2 :

Solve for x :

log1/5x  =  3

Solution :

log1/5x  =  3

Convert to exponential form.

x  =  (1/5)3

x  =  13/53

x  =  1/125

Problem 3 :

Solve for x :

logx125√5  =  7

Solution :

logx125√5  =  7

Convert to exponential form.

125√5  =  x7

5 ⋅ 5 ⋅ 5 ⋅ √5  =  x7

Each 5 can be expressed as (⋅ 5).

Then,

√5 ⋅ √5 ⋅ √5 ⋅ √5 ⋅ √5 ⋅ √5 ⋅ √5  =  x7

√57  =  x7

Because the exponents are equal, bases can be equated.

x  =  √5

Problem 4 :

Solve for x :

logx0.001  =  -3

Solution :

logx0.001  =  -3

Convert to exponential form.

0.001  =  x-3

1/1000  =  1/x3

Take reciprocal on both sides.

1000  =  x3

103  =  x3

Because the exponents are equal, bases can be equated.

10  =  x

Problem 5 :

Solve for x :

log5(5log3x)  =  2

Solution :

log5(5log3x)  =  2

Convert to exponential form.

5log3x  =  52

5log3x  =  25

Divide each side by 5.

log3x  =  5

Convert to exponential form.

x  =  35

x  =  243

Problem 6 :

Solve for x :

x + 2log279  =  0

Solution :

x + 2log279  =  0

x  =  -2log279

x  =  log279-2

Convert to exponential form.

27x  =  9-2

(33)x  =  (32)-2

33x  =   3-4

Because the bases are equal, exponents can be equated.

3x  =  -4

x  =  -4/3

Problem 7 :

If 2logx  =  4log3,  then find the value of x.

Solution :

2logx  =  4log3

Divide each side by 2.

logx  =  (4log3) / 2

logx  =  2log3

logx  =  log32

logx  =  log9

x  =  9

Problem 8 :

If 3x is equal to log(0.3) to the base 9, then find the value of x.

Solution :

From the information given, we have

3x  =  log9(0.3)

Solve for x.

3x  =  log9(1/3)

3x  =  log91 - log93

3x  =  0 - log93

3x  =  - log93

3x  =  - 1 / log39

3x  =  - 1 / log332

3x  =  - 1 / 2log33

3x  =  - 1 / 2(1)

3x  =  -1/2

x  =  -1/6

Problem 9 :

Solve for x :

log5 √(7x - 4) - 1/2  =  log5 √(x + 2)

Solution :

log5 √(7x - 4) - 1/2  =  log5 √(x + 2)

Subtract log5 √(x + 2) from each side.

log5 √(7x - 4) - log5 √(x + 2) - 1/2  =  0

log5 √(7x - 4) - log5 √(x + 2)  =  1/2

Use quotient rule.

log5[√(7x - 4) / √(x + 2)]  =  1/2

Convert to exponential form.

[√(7x - 4) / √(x + 2)]  =  51/2

(7x - 4) / (x + 2)  =  √5

Square each side.

(7x - 4) / (x + 2)  =  5

Multiply each side by (x + 2).

7x - 4  =  5 (x + 2)

7x - 4  =  5x + 10

Subtract 5x from each side.

2x - 4  =  10

2x  =  14

Divide each side by 2.

x  =  7

Problem 10 :

Solve for x :

log3x + log9x + log81x  =  7/4

Solution :

log3x + log9x + log81x  =  7/4

(1 / logx3)  +  (1 / logx9)  +  (1 / logx81)  =  7/4

(1 / logx3)  +  (1 / logx9)  +  (1 / logx81)  =  7/4

(1 / logx3)  +  (1 / logx32)  +  (1 / logx34)  =  7/4

(1 / logx3)  +  (1 / 2logx3)  +  (1 / 4logx3)  =  7/4

(4 / 4logx3)  +  (2 / 4logx3)  +  (1 / 4logx3)  =  7/4

(4 + 2 + 1) / 4logx3  =  7/4

7 / 4logx3  =  7/4

Multiply each side by 4/7.

1 / logx3  =  1

log3x  =  1

Convert to exponential form.

x  =  31

x  =  3 After having gone through the stuff given above, we hope that the students would have understood how to solve logarithmic equations.

Apart from the stuff given in this section, if you need any other stuff in math, please use our google custom search here.

You can also visit our following web pages on different stuff in math.

WORD PROBLEMS

Word problems on simple equations

Word problems on linear equations

Algebra word problems

Word problems on trains

Area and perimeter word problems

Word problems on direct variation and inverse variation

Word problems on unit price

Word problems on unit rate

Word problems on comparing rates

Converting customary units word problems

Converting metric units word problems

Word problems on simple interest

Word problems on compound interest

Word problems on types of angles

Complementary and supplementary angles word problems

Double facts word problems

Trigonometry word problems

Percentage word problems

Profit and loss word problems

Markup and markdown word problems

Decimal word problems

Word problems on fractions

Word problems on mixed fractrions

One step equation word problems

Linear inequalities word problems

Ratio and proportion word problems

Time and work word problems

Word problems on sets and venn diagrams

Word problems on ages

Pythagorean theorem word problems

Percent of a number word problems

Word problems on constant speed

Word problems on average speed

Word problems on sum of the angles of a triangle is 180 degree

OTHER TOPICS

Profit and loss shortcuts

Percentage shortcuts

Times table shortcuts

Time, speed and distance shortcuts

Ratio and proportion shortcuts

Domain and range of rational functions

Domain and range of rational functions with holes

Graphing rational functions

Graphing rational functions with holes

Converting repeating decimals in to fractions

Decimal representation of rational numbers

Finding square root using long division

L.C.M method to solve time and work problems

Translating the word problems in to algebraic expressions

Remainder when 2 power 256 is divided by 17

Remainder when 17 power 23 is divided by 16

Sum of all three digit numbers divisible by 6

Sum of all three digit numbers divisible by 7

Sum of all three digit numbers divisible by 8

Sum of all three digit numbers formed using 1, 3, 4

Sum of all three four digit numbers formed with non zero digits

Sum of all three four digit numbers formed using 0, 1, 2, 3

Sum of all three four digit numbers formed using 1, 2, 5, 6 